علم الدلالة بين العرب والغربيين - بصل, محمد; محجازي, فاتن; غفر, زيداء (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يشكل علم الدلالة ذروة الدراسات اللغوية التي وصل إليها علماء اللغة . ويلتقي في هذا العلم علماء الغرب مع علماء العربية القدماء في كثير من موضوعاته وعناصره ، إلا أن تلك البحوث لم تكن مؤطرة بإطار علم الدلالة بمفهومه اليوم بل جاءت مبثوثة في كتبهم اللغوية والنقدية أثناء معالجتهم قضايا اللغة بشكل عام . ومجال علم الدلالة ينحصر في اللسانيات فقط لأنه العلم الذي يدرس العلامات الدلالية بين العلاقات اللغوية ومدلولاتها في أي نص والظروف والملابسات المحيطة بهذا النص بهدف الوصول إلى المعنى مركزا على البعد الاجتماعي للحدث الكلامي . وقد اختلف الباحثون الغربيون في هذا المجال ، فمنهم من يرى أن موضوع علم الدلالة هو دراسة المعنى المعجمي للألفاظ ، ومعناها ضمن هذا الإطار هو المعنى المحدد والثابت لها ، ولا علاقة للسياق في تحديد معناها. في حين يرى باحثون آخرون أن علم الدلالة يهتم بتراكيب العلامات التي تظهر في الألسن الطبيعية ، وبتقصي العلاقات الدلالية بين العلاقات اللغوية ، على أن تنتظم هذه العلاقات في السياق الكلامي المحدد لمعناها . وقد استطاع علم الدلالة الغربي في الآونة الأخيرة أن يشق طريقه في التطور ويخرج من الأفكار القديمة التي حددت له في بدايته وأعني بها انتقال الدراسة التاريخية لدلالة الألفاظ إلى الدراسة الوصفية التي تدرس المعنى وعلاقاته وأنظمته في فترة زمنية ثابتة . Semantics forms the highest point linguistics which linguists have reached. In this domain the western linguists meet with the old Arab linguists in many of its subjects and items although those researches were not framed in the semantic frame, but they were various in their linguistical critical books during their study to the language issues in general. The semantics field is limited to linguistics only because it is the science which studies the semantic relations among the linguistic signs and its denotations in any text and the conditions and the surrounding circumstances of this text in order to reach meaning which emphasizes the social effect of speech. westerns Researchers disagreed in this field. Some of them think that semantics is the study of the dictionary meanings of vocabulary and their meanings field is the meaning in its definite meaning and the context has nothing to do with its meaning. Other researchers believe that semantics concentrates on the formation of signs which appear in the natural tongues and to study the semantic relations a mong the linguistic signs. So that these signs arranged in the speech context which decides its meaning. It is noteworthy that semantics could shoulder its way in development and get rid of the old thoughts which were decided for it at its beginning, and I mean the transition of the historical study of semantics into the descriptive study which studies the meaning and its relations and systems during a fixed period of time.